BANGKU (STOOL) UNTUK KAFE DENGAN LAHAN TERBATAS - Quartika, Ankie Ayu; Soedarwanto, Hady (Anggada : Jurnal Desain dan Seni, 2021)
Currently, cafe business is very popular especially in the capital city of Jakarta. However, most of the existing cafes tend to be small with limited space.the limited space size has an effect on the activities of café owners and employees in arranging seating in cafes. Meanwhile, for café visitors the effect on the comfort of sitting activities in cafes that thends to be long. For that we need a seat that can accommodate these activites. Based on the Virtuvius theory and data analysis process, a comfortable and practical Stool is needed. To ensure that the design meets the needs, data analysis process is carried out based on the principle of form follow function so that the design and structure of the Stool works well. The design of the Stool must have a character that is comfortable, easy to move, dan space saving so that it can make it easy for cafe owners and employees to tidy up and rearrange Stool s and provide sitting comfort for cafe visitors even for a long time.